The effect of adding toluene to increase the combustion efficiency of biodiesel - ÖZER, S. (Taylor and Francis Inc., 2020)
Many studies have been done to reduce diesel engine emissions due to the restrictions imposed on the emissions of diesel engines. Some of these studies focused on finding new fuels and using them in engines, while others focused on increasing the combustion efficiency of existing fuels. There are rare studies that report effects on engine emissions by mixing volatile and flammable chemicals such as toluene into motor fuels. Therefore, the aim of this study is to increase combustion efficiency and reduce emission values by adding toluene to diesel fuel and soybean oil biodiesel. For this purpose, 5% toluene was added to diesel and soybean biodiesel by volume. For this purpose, DT5 and SB5 fuel mixtures were created by adding 5% toluene by volume to diesel and soybean biodiesel. For each fuel mixture, the diesel engine was operated at a constant engine speed of 2600 rpm, at 25% (2.15 Nm), 50% (4.3 Nm), 75% (6.45 Nm) and 100% (8.6 Nm) engine loads. During the experiments, in-cylinder pressure changes exhaust gas temperature, fuel consumption value and exhaust emission values were measured. With the addition of toluene to the D100 fuel, the in-cylinder pressure value decreased by 4.32% in 100% engine load, while the SB100 fuel tended to decrease by 3.97%. With the addition of toluene at 100% engine load, CO and smoke opacity emissions decreased by 5.5%, 4.1%, compared to D100 fuel, while they decreased by 22.2%, and 14.4% compared to SB100 fuel. HC emissions have increased with the use of DT5 and SB5 fuels. The highest emission value in terms of HC emissions was measured as 40 ppm with DT5 fuel at 25% engine load. NOx emissions, on the other hand, increased at all engine loads. The highest increase was seen in 20% engine load on DT5 fuel with a ratio of 10.6%. © 2020, © 2020 Taylor & Francis Group, LLC.
2-s2.0-85087130156
Keywords: combustion efficiency; diesel engine; emission and performance; soybean oil biodiesel; Toluene